(untitled) (Journal of Medical & Health Sciences Review, 2025)
Endometriosis is a persistent gynecological disorder affecting millions of females worldwide, characterized by the growth of endometrial tissue outside the uterus. This condition leads to symptoms such as pelvic pain, dysmenorrhea, and infertility, significantly impacting quality of life. Recent studies have suggested a potential link among the microbiome and endometriosis symptoms, highlighting the importance of exploring this relationship further. Objective: To investigate the relationship among the microbiome and endometriosis symptoms, quality of life, and potential therapeutic implications in women. Methods:This cross-sectional study aimed to explore the relationship between the microbiome and endometriosis. In this study, 100 women (aged 25-35 years) were recruited that diagnosed with endometriosis using consecutive sampling method, from gynecology clinics in tertiary care hospitals. Endometriosis Health Profile-30 (EHP-30) was used to assess the quality of life. 16S rRNA sequencing was used to assess the analyze microbial diversity and composition. Results: Significant differences in microbial diversity and composition were observed between women with endometriosis and controls. 75% of participants reported moderate to severe pelvic pain. EHP-30 scores indicated significant impairment in quality of life, with mean scores of 65.4 ± 12.1. Specific microbial profiles correlated with symptom severity (r = 0.42, p < 0.001) and quality of life (r = -0.38, p < 0.01). Conclusion:This study highlights the potential role of the microbiome in endometriosis symptoms and quality of life. The findings suggest that alterations in the microbiome may contribute to the development and severity of endometriosis symptoms. Further research is needed to explore microbiome-targeted therapies and their potential to alleviate symptoms and improve quality of life for women with endometriosis.